2021
DOI: 10.1093/clinchem/hvab225
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Novel Troponin Algorithms for the Rule-Out of Non-ST-Elevation Acute Coronary Syndrome

Abstract: Background The European Society of Cardiology (ESC) rule-out algorithms use cutoffs optimized for exclusion of non-ST elevation myocardial infarction (NSTEMI). We investigated these and several novel algorithms for the rule-out of non-ST elevation acute coronary syndrome (NSTE-ACS) including less urgent coronary ischemia. Method A total of 1504 unselected patients with suspected NSTE-ACS were included and divided into a deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…67 In another study which compared new algorithms with the standard ESC-recommended algorithm used for ruling out NSTEMI based on cTn measurements, investigators found that a 0-1 h/0-3 h algorithm based on low baseline level and low variation had superior clinical sensitivity than the ESC algorithm: 95% vs. 65% for hs-cTnT and 87% vs. 64% for hs-cTnI. 68 The RAPID-TnT trial aimed to investigate the economic impact of the accelerated protocol for 0/1 h testing of hs-cTnT and found that despite an initial superior efficiency of the accelerated protocol, it led to no significant reduction of resource utilization compared to the standard 0/3 h protocol. Despite reducing the length of stay in the ED by 0.62 h per patient, the costs recorded were higher in the 0/1 h protocol arm by 472.49 USD per patient.…”
Section: Effectiveness Of Ctn Algorithms In Emergency Carementioning
confidence: 99%
“…67 In another study which compared new algorithms with the standard ESC-recommended algorithm used for ruling out NSTEMI based on cTn measurements, investigators found that a 0-1 h/0-3 h algorithm based on low baseline level and low variation had superior clinical sensitivity than the ESC algorithm: 95% vs. 65% for hs-cTnT and 87% vs. 64% for hs-cTnI. 68 The RAPID-TnT trial aimed to investigate the economic impact of the accelerated protocol for 0/1 h testing of hs-cTnT and found that despite an initial superior efficiency of the accelerated protocol, it led to no significant reduction of resource utilization compared to the standard 0/3 h protocol. Despite reducing the length of stay in the ED by 0.62 h per patient, the costs recorded were higher in the 0/1 h protocol arm by 472.49 USD per patient.…”
Section: Effectiveness Of Ctn Algorithms In Emergency Carementioning
confidence: 99%
“…Over time, the new high-sensitivity assays have improved diagnostic accuracy, being capable of detecting levels of cTn from 10 to 100 times lower than traditional tests. In this way, the high sensitivity cTn assays sped up the MI exclusion diagnostic process, thanks also to the introduction of several algorithms in the emergency room (ER) focused on its values at time 0 and after 1 or 2 h [2,[6][7][8][9][10]. Furthermore, the introduction of some clinical scores has improved the interpretation of the cTn values, even if not making them completely free from misunderstandings [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…UAP patients may differ from NSTEMI patients and typically have ischaemic cardiac disease being less available for revascularisation 9 10. They are typically ‘ruled-out’ by the ESC algorithms for non-ST segment elevation acute coronary syndrome (NSTE-ACS) 11 12. There is an ongoing debate on how this condition should be defined and what is the optimal treatment options after the implementation of high sensitivity troponin assays 13.…”
Section: Introductionmentioning
confidence: 99%